2018
DOI: 10.1021/acs.iecr.8b02426
|View full text |Cite
|
Sign up to set email alerts
|

Oleate-Based Protic Ionic Liquids As Lubricants for Aluminum 1100

Abstract: Because of their structures and tunable properties, viscosity among them, oleate-based protic ionic liquids (PILs) were used as lubricants for aluminum, aiming to apply them in metal forming processes. Three oleate-based PILs with three ammonium-based cations were tested as lubricants, in order to evaluate the influence of the cation structure on the tribological performance. Coefficient of friction (COF) determination and subsequent wear computations were conducted. Erichsen tests were also conducted to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Although the study of ILs in lubrication is dominated by AILs, the study of PILs and, in particular, halogen-free PILs as novel lubricants and lubricant additives is receiving the attention of tribological researchers [33,[35][36][37][38][39][40][41]. For instance, Zhao et al [41] synthesized a series of PILs having dodecyl-ammonium cations with S-(1-carboxylpropyl)-N,N-dialkyldithiocarbamate anions, where the alkyl group was either ethyl, butyl, or octyl.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study of ILs in lubrication is dominated by AILs, the study of PILs and, in particular, halogen-free PILs as novel lubricants and lubricant additives is receiving the attention of tribological researchers [33,[35][36][37][38][39][40][41]. For instance, Zhao et al [41] synthesized a series of PILs having dodecyl-ammonium cations with S-(1-carboxylpropyl)-N,N-dialkyldithiocarbamate anions, where the alkyl group was either ethyl, butyl, or octyl.…”
Section: Introductionmentioning
confidence: 99%
“…[11,13,17,18] PILs are thermally and chemically stable, so they can be recycled, which can make synthetic routes less expensive, more efficient, and environmentally less hazardous. [19,20] Due to all this versatility, PILs can be used in a wide range of applications such as an inert electrolyte to verify diffusivity of protective coatings, [21] lubricants, [22][23][24] nonaqueous plating systems, [25] catalysis, [26] fuel cells, batteries, [27] storage media for toxic gases, [28] performance additives in pigments, [29] and corrosion inhibitors. [7,30] In consequence, they have gained attention from many industries.…”
Section: Introductionmentioning
confidence: 99%
“…[27,31,32] The use of PILs as corrosion inhibitors is very promising, owing to their potentiality to be tailored for this application by modifying their structure. [23,33] It is vital to understand how structure makes them function as corrosion inhibitors. Compounds containing functional groups such as amines and carboxylic acids were investigated by Yoo et al, [12] Amin et al, [34] and Amin and Ibrahim, [35] and they were reported to present promising anticorrosion effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations